1999
DOI: 10.1099/13500872-145-4-955
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear rDNA phylogeny in the fungal genus Verticillium and its relationship to insect and plant virulence, extracellular proteases and carbohydrases

Abstract: Phylogenetic relationships among 18 isolates in the genus Verticillium, representing 13 species of diverse econutritional groups (pathogens of insects, plants, mushrooms, nematodes and spiders, and saprobes), were examined by using sequences from the internal transcribed spacer (ITS) and small nuclear (NS) rRNA regions. The isolates were also assessed for their abilities to infect insect larvae (Galleria mellonella) and to cause necrosis in alfalfa (Medicago sativa), and for their proteolytic, chitinolytic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
5

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 31 publications
(22 reference statements)
0
34
0
5
Order By: Relevance
“…Two opportunistic species have been thoroughly studied and tested as biocontrol agents: Pochonia chlamydosporia (Goddard) Zare and Gams (= Verticillium chlamydosporium) and P. lilacinus. These parasites grow in soil and may colonize the rhizosphere and the root (Kerry 1990;Siddiqui and Mahmood 1996;Bidochka et al 1999;Kerry 2000;Siddiqui et al 2000;Hirsch et al 2001;Khan et al 2001Khan et al , 2006Mukhtar and Pervaz 2003;Brand et al 2004). Both species have been used in the preparation of commercial formulations for the control of cyst and root-knot nematodes (Stirling et al 1998;Kerry 2000, Schenck 2004, Rumbos and Kiewnick 2006.…”
Section: Antagonistic Activity Of Fungal Chitinases On Nematode Eggsmentioning
confidence: 97%
“…Two opportunistic species have been thoroughly studied and tested as biocontrol agents: Pochonia chlamydosporia (Goddard) Zare and Gams (= Verticillium chlamydosporium) and P. lilacinus. These parasites grow in soil and may colonize the rhizosphere and the root (Kerry 1990;Siddiqui and Mahmood 1996;Bidochka et al 1999;Kerry 2000;Siddiqui et al 2000;Hirsch et al 2001;Khan et al 2001Khan et al , 2006Mukhtar and Pervaz 2003;Brand et al 2004). Both species have been used in the preparation of commercial formulations for the control of cyst and root-knot nematodes (Stirling et al 1998;Kerry 2000, Schenck 2004, Rumbos and Kiewnick 2006.…”
Section: Antagonistic Activity Of Fungal Chitinases On Nematode Eggsmentioning
confidence: 97%
“…All known serine proteinases of phy topathogens can be divided into trypsin like and subtil isin like enzymes. The first group contains proteinases that are produced by Cochliobolus carbonum [16], Verticillium dahliae [17,18], Stagonospora (Septoria) nodorum [19], and Phytophtora infestans [20] microorgan isms. Subtilisin like enzymes are secreted by C. carbonum [16], P. infestans [20], Acremonium typhium [21], Magnaporthe poae [22], Trichoderma harzianum [23], and Fusarium oxysporum [24].…”
mentioning
confidence: 99%
“…It has been suggested that FPI may have arisen from plant pathogens to escape competition via further specialisation in alternative hosts (Barron 1992;Bidochka et al 1999). FPI capabilities of changing hosts between invertebrates (insects or nematodes), endophytism and mycoparasitism could then be the consequences of this evolutionary process (Lopez-Llorca and Jansson 2006).…”
Section: Endophytism: Relevance In Biocontrol Performancementioning
confidence: 98%
“…Serine proteases from both nematophagous and entomopathogenic fungi seem to have a common ancestor, different from that of plant-parasitic fungi ). Production of subtilisins may be a retained character from a saprophytic ancestor, since subtilisin-like proteases are the principal broad-spectrum proteases produced by many saprophytes (Bidochka et al 1999).…”
Section: Lifestyle Overlappingmentioning
confidence: 99%
See 1 more Smart Citation